USE OF CARTOONS IN VALUES EDUCATION: SAMPLE OF SOCIAL UNITY AND SOLIDARITY VALUES - Abdullah Adıgüzel; İsmail Yüksel (Sakarya University, 2013)
Cartoons have widely been being used as an alternate approach for determining individuals' perceptions recently. Within this respect, study aims at determining secondary school students' perception about the social unity and solidarity values via cartoons. The participants of the study conducted as a qualitative research design and as a case study are 100 students from two different schools in two cities. The data of the study were collected through a data sheet consisted of a cartoon and four questions related to the cartoon. For analysing the data content analysis technique was administered and in this framework, the themes for each questions were defined. Frequencies for themes and subthemes were used for interpretations. The findings revealed that the great majority of the participants got the message of the cartoon correctly, felt sympathy, sorrow, unity and solidarity, love and respect, hope, peace, separation, and longing about the cartoon. The findings also manifested that the participants remarked the main values in the cartoon as social unity and solidarity, fellowship, friendship and social relations. Finally, the results indicated that they interpreted the message of the cartoon mostly with the proverbs such as "united we stand united we are stronger", "many hands make light work", and "no one is rich enough to do without his neighbour". As a result, the study revealed that the students understood the message of the cartoons correctly, supported their perceptions with the right words and proverbs, and also revealed that use of cartoons are strong alternative approach if used properly.